2013
DOI: 10.1530/eje-12-0688
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in serum high-molecular-weight adiponectin levels in metabolic syndrome

Abstract: Objective: The objective of this study was to estimate gender-specific associations between metabolic syndrome (MS) and high-molecular-weight (HMW) adiponectin in an Estonian adult population. Methods: Plasma HMW adiponectin was measured in 458 subjects (191 men) who participated in a population-based cross-sectional multicenter study (nZ495) on the prevalence of metabolic disorders in Estonia. MS was defined according to National Cholesterol Education Program Adult Treatment Panel III criteria. Results: Media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
4
27
0
Order By: Relevance
“…For example, elevated adiponectin levels were found to be associated with risk of fracture in older adult males but not in females (33). Adiponectin levels were also shown to be associated with various metabolic risk factors in females but not in males (34). Furthermore, gender differences were found in the association between adiponectin and longevity (20), insulin resistance (35) and BMI (36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, elevated adiponectin levels were found to be associated with risk of fracture in older adult males but not in females (33). Adiponectin levels were also shown to be associated with various metabolic risk factors in females but not in males (34). Furthermore, gender differences were found in the association between adiponectin and longevity (20), insulin resistance (35) and BMI (36).…”
Section: Discussionmentioning
confidence: 99%
“…The associations between adiponectin level and the components of the insulin-resistance syndrome (including BMI and glucose level) have been observed in both general population and patients with chronic kidney disease (Guebre-Egziabher et al, 2005;Tsao et al, 2008;Ramos et al, 2009;Lee et al, 2011;An et al, 2011;Eglit et al, 2012). In subjects with metabolic syndrome, patients with type 2 diabetes or coronary artery disease the serum total adiponectin level is reduced (Kacso et al, 2010;Hara et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Guebre-Egziabher et al showed that although serum adiponectin level increased when renal function was deteriorated in patients with CKD, at the same time its level was still more significantly influenced by BMI (Guebre-Egziabher et al, 2005). A number of studies (Ramos et al, 2009;Hara et al, 2011;Eglit et al, 2012) showed significant positive association of adiponectin with female gender in the population of patients with normal kidney function and with CKD, both on conservative treatment or those undergoing hemodialysis. In healthy subjects high adiponectin level appears to be protective against cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have indicated that the high-molecular-weight (HMW) form of adiponectin is its most active form [3], [5], [6]. Serum HMW adiponectin values are inversely correlated with the presence of metabolic syndrome in both genders [6], [7]. Analysis of the relationship between HMW adiponectin and components of metabolic syndrome have shown that HMW adiponectin is inversely associated with triglycerides, obesity and fasting glucose, and positively associated with HDL cholesterol [9][12].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the relationship between HMW adiponectin and components of metabolic syndrome have shown that HMW adiponectin is inversely associated with triglycerides, obesity and fasting glucose, and positively associated with HDL cholesterol [9][12]. There is clear gender difference in HMW adiponectin levels: women have significantly higher HMW adiponectin levels compared to men [7], [8]. The relationship between HMW adiponectin and blood pressure has varied between different studies and also by gender [9][12].…”
Section: Introductionmentioning
confidence: 99%